Pd@Py2PZ@MSN as a Novel and Efficient Catalyst for C–C Bond Formation Reactions - Sayahi, Mohammad Hosein; Toosibashi, Mansoureh; Bahmaei, Mehdi; Lijan, Hosein; Ma'Mani, Leila; Mahdavi, Mohammad; Bahadorikhalili, Saeed (Frontiers in Chemistry, 2022)
In this paper, a novel catalyst is introduced based on the immobilization of palladium onto dipyrido[3,2-a:2',3'-c]phenazine modified mesoporous silica nanoparticles. Dipyrido[3,2-a:2',3'-c]phenazine (Py2PZ) ligand is synthesized in a simple method from the reaction of 1,10-phenanthroline-5,6-dione and 3,4-diaminobenzoic acid as starting materials. The ligand is used to functionalize mesoporous silica nanoparticles (MSN) and to modify their surface chemistry for the immobilization of palladium. The palladium immobilized dipyrido[3,2-a:2',3'-c]phenazine modified mesoporous silica nanoparticles (Pd@Py2PZ@MSN) are synthesized and characterized by several characterization techniques, including TEM, SEM, FTIR, TGA, ICP, XRD, and EDS analysis. After the careful characterization of Pd@Py2PZ@MSN, the activity and efficiency of this catalyst is examined in carbon-carbon bond formation reactions. The results are advantageous in water and the products are obtained in high isolated yields. In addition, the catalyst shows very good reusability and did not show significant loss inactivity after 10 sequential runs.